The Impact of Climate Change Projections on Flood Vulnerability of Electrical Infrastructure in the Kapuas River Basin, West Kalimantan - Khotimah Ratna Indradjanue; Joni Hermana (Journal of Social Research, 2026)
Climate change has increased the frequency and intensity of extreme hydrometeorological events, particularly floods, which have the potential to disrupt the reliability of the electricity system in West Kalimantan. This study aims to examine historical rainfall conditions and projections until 2060, map flood risk in the Kapuas watershed, and assess its impact on the electricity system. Rainfall analysis was conducted using CMIP6 climate projection data based on the SSP1-2.6, SSP2-4.5, and SSP5-8.5 scenarios for the 2026–2060 period. Flood risk mapping was carried out spatially using the Weighted Linear Combination (WLC) approach, incorporating parameters such as rainfall, land slope, land cover, and soil texture. Furthermore, flood risk maps were overlaid with transmission infrastructure and substations in the Kapuas watershed to identify vulnerability levels. The results show that the Kapuas watershed will remain in the very wet climate category until 2060, with more than 300 rainy days per year and an increasing tendency for extreme rainfall intensity, especially under the SSP5-8.5 scenario. Flood risk mapping indicates that most areas of the Kapuas watershed consistently fall within the high to very high flood risk category, particularly in downstream and lowland regions. The overlay results reveal that more than 85% of transmission towers and nearly all substations are located within high flood risk zones.